BURNINGS AND FIRES IN THE MUNICIPALITY OF LÁBREA – AMAZONAS - Amâncio, Raimundo Nonato Duarte; Sitoie, Carlitos Luis (Seven Editora, 2025)
This study investigates fires and fires in the municipality of Lábrea, Amazonas, contextualizing the environmental problem in the Amazon region, where the practice of burning is frequently used in agriculture and other productive activities. The main objective of the research was to evaluate the causes that transform fires into fires. The methodology adopted includes structured interviews with social actors in the community, according to the principles of oral history, allowing a rich qualitative analysis of the experiences and memories of local residents. The work is based on three types of narrative: thematic interviews, life stories and oral traditions, which enabled a comprehensive understanding of the relationships between workers and environmental management practices. Furthermore, participant observation contributed to a better immersion in the social and cultural context of the interviewees. The results demonstrated that the historical relationship between workers and land and natural resources, combined with socioeconomic factors and market pressure, significantly influences the frequency and intensity of fires. The research concludes that, to mitigate the impacts of fires, it is essential to consider local knowledge and promote sustainable management practices that integrate the voices of communities in the formulation of public policies.DOI: https://doi.org/10.56238/sevened2025.029-113